Anti‐ganglioside antibodies in Guillain–Barré syndrome and chronic inflammatory demyelinating polyneuropathy in Chinese patients. Issue 4 (23rd December 2016) - Fan, Chenghe; Jin, Haiqiang; Hao, Hongjun; Gao, Feng; Sun, Yongan; Lu, Yuanyuan; Liu, Yuanyuan; Lv, Pu; Cui, Wei; Teng, Yuming; Huang, Yining
ABSTRACT: Introduction : In this study we investigated the relationships between anti‐ganglioside antibodies and Guillain–Barré syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy (CIDP). Methods : Samples from 48 Chinese patients diagnosed with GBS and 18 patients diagnosed with CIDP were retrospectively reviewed. Results : In the GBS patients, 62.5% were classified as having acute inflammatory demyelinating polyneuropathy (AIDP), 27.1% were found to have acute motor axonal neuropathy (AMAN), and 10.4% were unclassified. Serum IgG anti‐ganglioside antibodies were detected in 46.2% of the AMAN patients and in 6.7% of the AIDP patients ( P < 0.05); 5.6% of the 18 CIDP patients were IgG antibody positive, and 27.8% were IgM antibody positive. Facial palsy and sensory impairment were significantly associated with IgM antibodies. Conclusions : These results suggest that IgG anti‐GM1 antibodies are associated with AMAN, but not with AIDP, and that IgM antibodies against GM1, GM2, and GM3 are associated with facial nerve palsy. Muscle Nerve 55 : 470–475, 2017